Physiological measurement and evaluation of maximal aerobic capacity of professional male football players of the 2004 Chinese soccer league - Qin, Z. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Modern soccer is characterized by periods of "all-out" and "all-defend" and the deepening professionalization of World soccer have resulted in games being played at very high intensity.. It is obvious that modern soccer games require high demand of player`s physical efficiency. The research in this area indicates that aerobic capabilities are important for soccer players. This paper discloses the status quo of the male professional Chinese Soccer League`s aerobic capabilities and also analyzes the differences of aerobic capabilities of different levels of soccer players. Methods Eighteen soccer players of the WuHan HuBei professional football club were subjects and performed a load increase-by-degrees exercise test to determine the physiological index of their aerobic capability. Results The research determined the physiological index of aerobic capability and analyzed the differences between the aerobic capabilities of the male soccer players of different levels. Discussion / Conclusions The physiological index of aerobic capability of male professional football players of the Chinese Soccer League A Champion in 2004 was less than that of the excellent soccer players of other countries. The aerobic capability of players of different levels of sport has a significant difference.